Cultural Studies and Soft Skills: An Integrated Approach - BADAOUI, Bouchra (International Journal of Language and Literary Studies, 2024)
This paper aims to clear a space of critical intervention from within the discursive debates on soft skills by adopting a cultural studies approach and appropriating its precepts to develop what I call "the soft skilling process" which is a life-long experience of learning that denotes a mode of dwelling in a world of globalizing identities and travelling cultures, where identities are understood as being constantly on the move and in a process of becoming, emphasizing the postmodern notion of the creative performativity of identity. Instead of being static capabilities or fixed traits, soft skills must be inscribed within a multidimensional and developmental process in which individuals develop expertise in navigating and negotiating multiple cultural worlds and identities. My point is to shift the traditional focus from employability and professional skills, which is dominant in studies on soft skills, to a humanistic education that promotes cultural awareness, ethical responsibility, and sustainability: Openness to experience, active participatory learning, and biodiversity awareness are the objectives to reach this educational experience. The proposed educational framework aims to develop engineers who are not only technically skilled but also culturally and ethically aware global citizens.